Two national liberation movements compared: Oromia and the southern Sudan - Jalata, Asafa (Social justice, 2000)
Part of a special section on race, class, and state crime. The writer compares the national liberation movements of the Oromia and the southern Sudanese. He historically charts the emergence and development of these nationalisms and explains how resistance to colonial domination was transformed into the Oromo and southern Sudanese national movements. In addition, he compares the two movements in terms of their similarities and differences. Furthermore, he evaluates whether the principle of national self-determination is applicable to the conditions of these national liberation movements. Finally, he concludes that the Oromia and the southern Sudan must start to build good relations with each other without being manipulated into accepting temporary political advantages that forfeit their permanent gains.